On the Development of Space-Number Relations: Linguistic and Cognitive Determinants, Influences, and Associations - Nuerk, Hans-Christoph; Cipora, Krzysztof; Domahs, Frank; Haman, Maciej (Frontiers Media SA, 2020)
Space and numbers are closely linked to each other in the human mind and brain. These bidirectional links may be the end product of innate biases and/or developmental, educational, and acculturation processes. Whatever their origin may be, there is no doubt that space-number relationships are influenced by linguistic and other cognitive determinants in adults. Biological development, refinement of domain-general abilities like inhibition, working memory capacity, reasoning skills, embodied representations underlying spatial and/or numerical processes may create a basis for formation or restructuring of the links between space and numbers. In modern societies, all this happens in parallel to enculturation encompassing linguistic factors (e.g., reading / writing direction; grammatical number forms), cognitive factors that are not or only partially related to language (e.g., working memory, inhibition) and those that are explicitly related to formal math education and culture (e.g., teaching a number line, individually, culturally or religiously (dys-)preferred numbers like 3, 8, 12, or 13). However, such processes neither begin nor end with adulthood, but continue developing through the lifespan. The associations between space and numbers seems to vary across lifetime development: some space-number relationships become weaker with age so that it is easier to inhibit processing of irrelevant spatial / numerical features in conflicting stimuli. On the other hand, some space number associations are strengthened in lifetime development, possibly due to longer exposure to cultural factors, as well as due to decrease in efficiency of inhibition mechanism. A better theoretical distinction is needed to differentiate the development of different types of space-number relationships over the lifetime. For instance, an important distinction in such models is the distinction between directionality of space-number relations (e.g., SNARC effect) and extension of spatial and numerical magnitudes, such as conflicts between spatial and numerical codes in Approximate Number System (ANS) tasks, where different numerosities (and hence different visually corresponding aspects) have to be compared.